Costing Methods: Selection and Application in a Metalworking Company - de Souza, John Cesar (2019)
In a scenario of great competition between companies, and where the country's economy is not favorable to new investments, it is difficult to stand out from competitors and gain greater market representation. Besides being prominent in the market, every company looks for a way to become more profitable. All of this is directly linked to the company's strategic decisions and how they will be achieved. In order to achieve a successful strategy, it is essential to have concrete information that can be used as a basis for decision-making. A very important data for strategies linked to the profitability of the business is to know the real cost of your product. This work is an applied research, conducted through a case study, which aims to present the choice and use of a costing method for the cost determination and cost management of the company. It also presents the process of choosing the method to be used and some difficulties in its implementation. The costing method selected was absorption costing, which is a traditional method and through it, it was possible to find a cost 42.5% higher than that practiced by the company.